2023
DOI: 10.18517/ijaseit.13.2.17581
|View full text |Cite
|
Sign up to set email alerts
|

Bioremediation Performance of Marine Sponge Symbiont Bacteria against Nickel and Mercury Heavy Metal Pollutants

Abstract: Heavy metals, mercury, and nickel are toxic contaminants, forming positive ions when concentrated and dissolved, and can accumulate in a specific object, including water. The activity and performance of bacterial bioremediation against toxic heavy metals vary due to bacterial characteristics and internal contaminant factors. This research aims to analyze the activity, performance, and efficiency of bioremediation of nickel and mercury pollutants using marine sponge symbiont bacteria. The bioremediation analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 61 publications
0
0
0
Order By: Relevance
“…Using Nonpolar Solvents Diethyl-ether solvent is a nonpolar solvent group but has different characteristics from other nonpolar solvents. Based on the chemical structure, diethyl-ether (C2H5-O-C2H5) has a constituent element in the form of the element oxygen which has two pairs of free electrons, causing diethyl-ether to have a relatively high degree of reactivity [7], [15], [44]. Thus, 3a 1 2 3b…”
Section: Analysis Of the Chemical Components Of Sponge Extractsmentioning
confidence: 99%
See 2 more Smart Citations
“…Using Nonpolar Solvents Diethyl-ether solvent is a nonpolar solvent group but has different characteristics from other nonpolar solvents. Based on the chemical structure, diethyl-ether (C2H5-O-C2H5) has a constituent element in the form of the element oxygen which has two pairs of free electrons, causing diethyl-ether to have a relatively high degree of reactivity [7], [15], [44]. Thus, 3a 1 2 3b…”
Section: Analysis Of the Chemical Components Of Sponge Extractsmentioning
confidence: 99%
“…Previous research on this topic has reported that several marine animals, such as sea stars and sponges, have medicinal value [13], [14]. This can be seen in the antibacterial activity of the sponge extract against pathogenic bacteria and parasitic fungi, such as the ability to inhibit the growth of Staphylococcus aureus, Bacillus subtilis, Salmonella thypi, and Escherichia coli, Candida albicans [15], [16], [17]. The results of other studies also report that sponge extract can inhibit the growth of disease-causing enzymes; for example, it has Acetylcholinesterase activity, an enzyme that can lead to a weakening of the ability to think in humans [18], [17], [18].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation